Adverse effects of beta-blockade withdrawal in patients with congestive cardiomyopathy. - Swedberg, K (1980)
Fifteen patients with congestive cardiomyopathy who had improved conspicuously on chronic administration of a beta-blocker were studied after withdrawal of the drug. In six patients there was a pronounced deterioration of their clinical condition, and in all of the remaining patients there was a significant decrease in ejection fraction, and signs of compromised diastolic function with pathological apex curves and an increase in third heart sound. All these changes were reversed within a few weeks to a few months after readministration of beta-blocking drugs. This study supports the idea that an aetiological factor in congestive cardiomyopathy may be a pathological response to sympathetic stimulation which could be partly controlled by administration of beta-blocking drugs.